The vicissitudes of the delimitation of the intangible area and the legal physical sanitation of Punchauca and its reality in the Bicentennial, 1945-2021 - Quispe Pastrana, Edgar (2020)
The house and chapel of the old Punchauca hacienda was declared a National Monumental Heritage Site in 1980. This recognition was given for having been the site, during the independence period, of the interview between the Liberator José de San Martín and the viceroy José de la Serna. However, after this declaration, the National Institute of Culture and today the Ministry of Culture have done little to carry out a complete delimitation of the intangible area, the legal physical sanitation, and to carry out an integral project of recovery and restoration of the monument, and its subsequent execution. Moreover, in recent years, the building has been cut down, affecting the integrity of the monument. In this sense, with the Bicentennial approaching and according to institutional documents of the State, we reviewed the actions carried out in Punchauca.